Xicoténcatl - Varela, Félix, 1788-1853.; Forero Quintero, Gustavo (Madrid : Iberoamericana ; Frankfurt am Main : Vervuert ; Mexico D.F.: Bonilla Artigas editores, 2012)
As Spain's New World colonies fought for their independence in the early nineteenth century, an anonymous author looked back on the earlier struggle of native Americans against the Spanish conquistadores and penned this novel, Xicoténcatl. Writing from a decidedly anti-Spanish perspective, the author describes the historical events that led to the march on Tenochtitlán and eventual conquest of the Aztec empire in 1519 by Hernán Cortés and his Indian allies, the Tlaxcalans. Xicoténcatl stands out as a beautiful exposition of an idealized New World about to undergo the tremendous changes wrought by the Spanish Conquest.
Includes bibliographical references and indexes.
Basado en un facsímil de la primera edición publicada por Guillermo Stavelly en Fildadelfia en el año de 1826 cotejado con la versión de Antonio Castro Leal (1964) y con la de Luis Leal y Rodolfo J. Cortina (1995).
Keywords: Cortés, Hernán, -- 1485-1547 -- Fiction; Electronic books